Optimization Analysis of Petroganik Fertilizer Distribution at PT Petrokimia Gresik - Muhammad Dwi Naffiqi Nugraha; Muhammad Jihadi; Baroya Mila Shanty (Universitas Muhammadiyah Malang, 2021)
The purpose of this study was to evaluate the company's initial distribution channel for distribution optimization to reduce the high distribution costs of PT Petrokimia Gresik. Petroganic fertilizer is one of the company's products, which currently increases its production, so it is necessary to implement a good distribution system to optimize transportation costs. The analytical tool used is the transportation method, where the company's initial allocation is recalculated using the Least Cost method, double-checking to find out whether it is optimal with the Modified Distribution (MODI) method. From the results of this study, it is known that the company's initial transportation costs incurred by the company when using the Least Cost method, there is cost transmission and optimization with the Modified Distribution method resulting in an optimal cost reduction value. The difference in distribution costs was obtained by 11.7% of the total costs incurred. The suggestion is that companies can consider transportation methods as a decision-making policy to optimize costs in their distribution system.